Development and Validation of a LC-MS/MS Method for the Determination of Nitrofuran Metabolites in Soft-Shell Turtle Powder Health Food Supplement - EunChae Ryu; Ji Sung Park; Sib Sankar Giri; Se Chang Park (International Journal of Analytical Chemistry)
Soft-shell turtle (SST; freshwater terrapin or tortoise) is a popular and important health functional food (HFF) product in many Asian countries. HFFs containing SST must be safe, but several HFFs have been found to be contaminated with dangerous substances, such as nitrofuran metabolites (NFMs). This finding suggests that the consumption of HFFs results in the regular exposure of vulnerable individuals to hazardous substances. Importantly, nitrofuran antibiotics have been banned for use in food-producing animals since the 1990s by the European Union. Thus, in this study, we propose a reliable and quick method to reduce the time required for the detection of four NFMs in SST powder that conventional methods are unable to quantify. Our method involves the derivatization and hydrolysis of SST powder and was validated in accordance with the requirements of European Commission Decision 2002/657/EC. The method achieves an apparent mean recovery of 82.2–108.1%, repeatability of 1.5–3.8%, and reproducibility of 2.2–4.8% for 0.5–10.0 μg kg−1 of 1-aminohydantoin, semicarbazide, 3-amino-2-oxazolidinone, and 3-amino-5-morpholinomethyl-2-oxazolidinone. In addition, linearity was achieved with correlation coefficients of 0.999, and the detection capability (CCβ) and decision limit (CCα) were found to be reliable, indicating that this is a fast and accurate method for the analysis of SST powder. The validated method was successfully applied to detect NFMs in SST powder in commercial HHFs.